APLIKASI MOBILE-CUSTOMER RELATIONSHIP MANAGEMENT UNTUK SMALL AND MEDIUM SIZE ENTERPRISES (SMEs) - Utaminingsih Linarti (Jurusan Teknik Informatika, 2015)
The key factor of enterprise in order to still growth and developed is customer. The customer will give the value to the enterprise in the form of profit. Therefore, enterprises must be able to establish an sustainable relationship to customer. Since 1990 began to develop what is called Customer Relationship Management (CRM). CRM implements between the development of information technology and customer-centric views. The development of technology and the human need's to move quickly, CRM evolved into a mobile CRM. The Internet make mobile-CRM easily used to all of enterprise, especially small and medium size enterprise. This article is aim to explain the role and the applicability of mobile CRM to business level conditions of small and medium size enterprises (SMEs). The presence of mobile phone operating system that is flexible (android system), the internet cost of affordable and the social media applications as analogy of user interface in making mobile CRM application. CRM mobile application can be downloaded or installed through the app store with ease. It encourages mobile-CRM benefit's rather than as a function of customer data collection but became a window for customer information. In addition, the database can be analysis and relate to customer activity. Mobile CRM applications can take advantage of cross selling methods.